Non-Destructive Evaluation of Hidden Defects Beneath the Multilayer Organic Protective Coatings Based on Terahertz Technology - Tu, Wanli; Zhong, Shuncong; Luo, Manting; Zhang, Qiukun (Frontiers in Physics, 2021)
Organic protective coating system play an important role for corrosion protection of offshore metallic structures. It is of practical importance to detect possible coating defects and evaluate coating performance for corrosion degradation monitoring. Reliable defect identification can provide timely and effective maintenance to avoid serious consequences. This work investigated various mulitilayer organic coating system by terahertz pulse imaging technology, aim to explore the inspection ability of terahertz non-destructive testing (THz NDT) of protective coating. Several types of defective coating samples were measured. The comparison of measurements obtained for sites with and without defects was provided. The changes in the signals caused by the presence of defects were explained. Structural analysis, quantitative evaluation and defect identification were carried out in detail. The results of measurements showed that corrosion defect, paint bulge defect and paint detachment defect can be distinguished and identified by combination with the causes of defect. It can provide effective technical guidance for terahertz technology gradually extended to engineering application.